Fabric-Type Flexible Energy-Storage Devices for Wearable Electronics - Siwei Xiang; Long Qin; Xiaofei Wei; Xing Fan; Chunmei Li (Energies, 2023)
With the rapid advancements in flexible wearable electronics, there is increasing interest in integrated electronic fabric innovations in both academia and industry. However, currently developed plastic board-based batteries remain too rigid and bulky to comfortably accommodate soft wearing surfaces. The integration of fabrics with energy-storage devices offers a sustainable, eco-friendly, and pervasive energy solution for wearable distributed electronics. Fabric-type flexible energy-storage devices are particularly advantageous as they conform well to the curved body surface and the various movements associated with wearing habits such as running. This review presents a comprehensive overview of the advances in flexible fabric-type energy-storage devices for wearable electronics, including their significance, construction methods, structure design, hybrid forms with other energy sources, and the existing challenges and future directions. With worldwide efforts on materials and technologies, we hope that progress in this review will revolutionize our way of life.